Superior capsule reconstruction stabilizes the humeral head during scaption: in vivo 3-dimensional kinematic analysis using model–image registration - Hamada, Hiroshige; Matsuki, Keisuke; Kamijo, Hideki; Hoshika, Shota; Deguchi, Tomohiko; Takahashi, Norimasa; Sugaya, Hiroyuki; Banks, Scott A. (JSES international, 2025)
It has been proven that superior capsule reconstruction (SCR) improves the superior translation of the humeral head through cadaveric studies. However, there has been limited information on in vivo glenohumeral kinematics of shoulders with SCR. The purpose of this study was to compare pre- and postoperative glenohumeral kinematics in shoulders that underwent arthroscopic SCR using model–image registration techniques. Patients who were planned for arthroscopic SCR using the fascia lata autograft due to irreparable massive rotator cuff tears were recruited for this study. The exclusion criteria were (1) preoperative active abduction <60°, (2) massive graft failure on postoperative magnetic resonance imaging, and (3) low image quality. Fluoroscopic images were recorded during active scaption pre- and postoperatively. Computed tomography was performed to create three-dimensional models of the humerus and scapula. Using these fluoroscopic images and three-dimensional models, three-dimensional shoulder kinematics were measured using model–image registration techniques. Pre- and postoperative glenohumeral kinematics and scapulohumeral rhythm were statistically compared. Shoulder ranges of motion and the American Shoulder and Elbow Surgeons scores were also compared. Twenty-five shoulders were included in this study, and 10 shoulders were excluded: graft failure, 4 shoulders; insufficient shoulder elevation, 5 shoulders; low image quality, 1 shoulder. The subjects of this study were 15 shoulders (9 males and 6 females) with a mean age of 63 years (range, 53-70). Flexion and the American Shoulder and Elbow Surgeons score significantly improved after surgery (P = .03 and < .001, respectively). There were no significant postoperative changes in glenohumeral rotations and scapulohumeral rhythm. The superior/inferior position of the humeral head from 10° to 90° of humeral abduction also showed no significant postoperative change; however, the change in humeral position from 30° was significantly smaller after surgery than before surgery (P = .03). No significant changes were observed in glenohumeral rotations and scapulohumeral rhythm after arthroscopic SCR. The superior/inferior humeral translation at humeral abduction greater than 30° was significantly smaller after surgery. These findings suggest that SCR stabilizes the humeral superior/inferior translation without alteration of glenohumeral rotation kinematics.